BREEDING AND GENETIC ESTIMATION OF SPRING BREAD WHEAT POPULATIONS OF THE SIBERIAN SHUTTLE BREEDING NURSERY OF CIMMYT - V. P. Shamanin; A. I. Morgunov; J. Manes; Y. I. Zelensky; A. S. Chursin; M. A. Levshunov; I. V. Pototskaya; I. E. Likhenko; T. A. Manko; I. I. Karakoz; A. V. Tabachenko; S. L. Petukhovsky (Вавиловский журнал генетики и селекции)
Shuttle breeding contributes much to the breeding to common wheat varieties resistant to adverse environmental factors by involving new sources of valuable biological and economical features from the world’s gene pool. Annually, 360 to 1000 lines and hybrid populations of spring bread wheat are studied in the Siberian shuttle breeding nursery (SSBN), established according to the shuttle breeding program participated by scientific institutions of West Siberia, Kazakhstan and the International Maize and Wheat Improvement Centre CIMMYT. Stable forms resistant to fungal diseases in West Siberia have been selected. The breeding value of the population created in the shuttle breeding program is shown. The results of evaluation of the collection of spring bread wheat varieties, breeding material and isogenic lines with Sr genes for resistance to Siberian populations of stem rust races under the conditions of the Omsk State Agrarian University experimental field and to the virulent race Ug 99 are presented. We have raised the most competitive hybrid populations of spring bread wheat resistant to a wide range of races of stem and leaf rust, including a virulent race Ug99. They can be used in different regions in case of global dispersal of stem rust.